Building Bilingual- Glossary to keep Translations and writings swift and consistent - Sheliyna, S. (My University, 2021)
Lexicography, as a sub field of Linguistics, involves compiling, writing or editing of Dictionaries, Glossaries, Thesaurus etc. In its both forms of Theoretical and Practical types, the discipline serves as the reliable source of information for language users. Glossaries as a part of Lexicography, developed by the Lexicographers of several fields to fulfill the language needs of scholars and users of such particular area of subject. Hence, in compiling bilingual glossary several semantic problems are encountered by the lexicographers such as problems in finding translation equivalents particularly cultural equivalents, meaning discrimination, and equivalents of idioms, and proverbs. Qualitative methodology is used to identify the ways and meanings of overcoming the problems. Accordingly, comparative methodology is used to compare the relevancy of the head words and the translation equivalents and descriptive methodology is used to describe the study. This study aims at analyzing the effective ways of building bilingual glossaries to keep Translators/ Language facilitators swift and consistent. Importance of Glossary setting speaks in favour of difference between Dictionaries and Glossaries and unique features of Bilingual Glossaries. Procedures adapted by the Lexicographers/ Translators analyze the three procedures such as Transliteration, Translation and Coining of New Words which are widely used to build Bilingual-Glossaries. Finally, glossaries as a tool for eliminating uncertainty for Translators its, Characteristics are discussed. This study will help the students of Translation Studies and the researchers of Bilingual-Glossary making.
Keywords: Bilingual- Glossaries; Lexicographers; Translation